Nylon Suture Loop for Tagging Lymphatic Channels during Lymphaticovenular Anastomosis - Grace Hui-Min Tan; Jiajun Feng; Yee Onn Kok; Pearlie Woon Woon Tan; Allen Wei-Jiat Wong (Indian Journal of Plastic Surgery)
Background Lymphaticovenular anastomosis (LVA) requires special supermicrosurgery techniques designed for vessels less than 0.8 mm in size. While preparing the field for LVA, it is often difficult to handle the lymphatic vessel directly without injuring it or fracturing it entirely.